The role of financial institutions towards affordable housing to urban middle income earners: Evidence from Kampala City, Uganda - Atuheire, Kenneth; Kagambirwe Karyeija, Gerald (African Journal of Social Work, 2014)
The general objective of the study was to assess the role of financial institutions towards affordable housing to middle income earners in Kampala City. A sample size of 113 respondents was selected using both probability and non-probability sampling methods. Data was collected and analysed using mixed methods. Findings revealed a weak positive effect (=.312) of mortgage financing towards affordable housing and accounted for 9.7% change in affordable housing. This study also established a moderate positive effect (=.472) of housing loans towards affordable housing and accounted for 22.3% change in affordable housing. Findings further revealed a weak positive effect (=.345) of housing finance on affordable housing and contributed to 11.9% change towards affordable housing. Three major conclusions are made, i.e. a) when access is limited to mortgage financing, access to affordable housing is also limited and need for housing loans arises because they make great sense from a long-term savings perspective. These are useful to social work because the provision of housing extends across all of social work’s various arenas of endeavour, and Uganda is struggling to use housing finances to overcome the housing deficit. Additionally, social work research related to overcoming urban housing deficits adds knowledge to the way Africa is working to meet housing needs for the urban middle class.
Keywords: Affordable housing; Financial institutions; Middle income earners